The Influence of Work Environment and Work Motivation on the Work Loyalty of I-03 Military Court Employees - Rizqa Kinta Mani Marunduri; Rice Haryati; Susi Yuliastanty (Jurnal Riset Manajemen, 2024)
This study aims to analyze and find out the influence of the work environment, and work motivation on the work loyalty of Employees of the I-03 Padang Military Court. The data collection techniques used are observation, interviews and questionnaires. The type of data is quantitative data with primary and secondary data sources. The population used in this study is 30 employees of the I-03 Padang Military Court using Total Sampling, the number of samples in this study is 30 employees. The data analysis method in this study uses multiple linear regression analysis, determination coefficients and hypothesis testing of t-test and F-test. The results of this study show that: (1) The work environment has a positive and insignificant effect on the work loyalty of employees of the I-03 Padang Military Court (2) Work motivation has a positive and significant effect on the work loyalty of the employees of the I-03 Padang Military Court (3) The work environment (X1) and work motivation (X2) together have a positive and significant effect on the work loyalty of employees of the I-03 Padang Military Court. (4) The contribution of the independent variables of work environment (X1) and work motivation (X2) together to the dependent variable of work loyalty (Y) was 0.334 or 33.4%. The contribution of independent variables provides minimal explanation for dependent variables. While the remaining 66.6% was influenced by other variables outside this study.